2016
DOI: 10.1007/s11011-016-9867-1
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of novel mutations in maple syrup urine disease patients from Iran

Abstract: Maple Syrup Urine Disease (MSUD) is a rare autosomal recessive disorder of branched-chain amino acid (BCAA) metabolism. The disease is mainly caused by mutations either in the BCKDHA, BCKDHB, DBT or DLD genes encoding components of the E1α, E1β, E2 and E3 subunits of branched-chain α-keto acid dehydrogenase complex (BCKDC), respectively. BCKDC is a mitochondrial enzyme which is responsible for the normal breakdown of BCAA. The rate of consanguineous marriage in Iran is 38.6 %, so the prevalence of autosomal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, Quental et al [ 6 ], in a study with 30 Portuguese patients, found 17 mutations with no difference in the frequency of these genes, with six in the BCKDHA gene, five in the BCKDHB gene, and six in the DBT gene. A study published by Abiri et al [ 27 ] investigating 20 Iranian families of MSUD patients, six patients demonstrated homozygous haplotype for the BCKDHA gene, nine for the BCKDHB gene, and two for the DBT gene. Gupta et al [ 28 ], studying 24 unrelated Indian patients, found 20 mutations in 22 of the patients, with 11 novel mutations—four in the BCKDHA gene, six in the BCKDHB gene, with a novel mutation identified in the DBT gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, Quental et al [ 6 ], in a study with 30 Portuguese patients, found 17 mutations with no difference in the frequency of these genes, with six in the BCKDHA gene, five in the BCKDHB gene, and six in the DBT gene. A study published by Abiri et al [ 27 ] investigating 20 Iranian families of MSUD patients, six patients demonstrated homozygous haplotype for the BCKDHA gene, nine for the BCKDHB gene, and two for the DBT gene. Gupta et al [ 28 ], studying 24 unrelated Indian patients, found 20 mutations in 22 of the patients, with 11 novel mutations—four in the BCKDHA gene, six in the BCKDHB gene, with a novel mutation identified in the DBT gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, Quental et al (5), in a study with 30 Portuguese patients, found 17 mutations with no difference in the frequency of these genes, with six in the BCKDHA gene, ve in the BCKDHB gene, and six in the DBT gene. A study published by Abiri et al (24) investigating 20 Iranian families of MSUD patients, six patients demonstrated homozygous haplotype for the BCKDHA gene, nine for the BCKDHB gene, and two for the DBT gene. Gupta et al (26), studying 24 unrelated Indian patients, found 20 mutations in 22 of the patients, with 11 novel mutations -four in the BCKDHA gene, six in the BCKDHB gene, with a novel mutation identi ed in the DBT gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, Quental et al 5, in a study with 30 Portuguese patients, found 17 mutations with no difference in the frequency of these genes, with six in the BCKDHA gene, ve in the BCKDHB gene, and six in the DBT gene. A study published by Abiri et al (24) investigating 20 Iranian families of MSUD patients, six patients demonstrated homozygous haplotype for the BCKDHA gene, nine for the BCKDHB gene, and two for the DBT gene. Gupta et al (26), studying 24 unrelated Indian patients, found 20 mutations in 22 of the patients, with 11 novel mutations -four in the BCKDHA gene, six in the BCKDHB gene, with a novel mutation identi ed in the DBT gene.…”
Section: Discussionmentioning
confidence: 99%